The Role of Pigments and Cryptochrome 1 in the Adaptation of Solanum lycopersicum Photosynthetic Apparatus to High-Intensity Blue Light - Aleksandr Ashikhmin; Pavel Pashkovskiy; Anatoliy Kosobryukhov; Alexandra Khudyakova; Anna Abramova; Mikhail Vereshchagin; Maksim Bolshakov; Vladimir Kreslavski (MDPI AG, 2024)
The effects of high-intensity blue light (HIBL, 500/1000 µmol m−2s−1, 450 nm) on Solanum lycopersicum mutants with high pigment (hp) and low pigment (lp) levels and cryptochrome 1 (cry1) deficiency on photosynthesis, chlorophylls, phenols, anthocyanins, nonenzymatic antioxidant activity, carotenoid composition, and the expression of light-dependent genes were investigated. The plants, grown under white light for 42 days, were exposed to HIBL for 72 h. The hp mutant quickly adapted to 500 µmol m−2s−1 HIBL, exhibiting enhanced photosynthesis, increased anthocyanin and carotenoids (beta-carotene, zeaxanthin), and increased expression of key genes involved in pigment biosynthesis (PSY1, PAL1, CHS, ANS) and PSII proteins along with an increase in nonenzymatic antioxidant activity. At 1000 µmol m−2s−1 HIBL, the lp mutant showed the highest photosynthetic activity, enhanced expression of genes associated with PSII external proteins (psbO, psbP, psbQ), and increased in neoxanthin content. This mutant demonstrated greater resistance at the higher HIBL, demonstrating increased stomatal conductance and photosynthesis rate. The cry1 mutant exhibited the highest non-photochemical quenching (NPQ) but had the lowest pigment contents and decreased photosynthetic rate and PSII activity, highlighting the critical role of CRY1 in adaptation to HIBL. The hp and lp mutants use distinct adaptation strategies, which are significantly hindered by the cry1 mutation. The pigment content appears to be crucial for adaptation at moderate HIBL doses, while CRY1 content and stomatal activity become more critical at higher doses.